Становлення та розвиток органів служби безпеки України (історико-правовий аналіз) - Грідін, О.В. (Держава і право, 2010)
Розглядаються питання становлення і розвитку Служби безпеки України. Аналізуються нормативноправові акти, які найбільш чітко відображають той чи інший

періоди розвитку даного інституту.

Ключові слова: Служба безпеки України, правове регулювання Рассматриваются вопросы становления и развития Службы безопасности Украины. Анализируются нормативноправовые акты, наиболее четко отражающие тот

или иной период развития данного института.

Ключевые слова: Служба безопасности Украины, правовое регулирование. In article questions of formation and development of Security service of Ukraine are considered, the author s periodization of studied institute is offered. Regulatory legal acts which
most accurately are considered reflect this or that period of development of the given institute.
The attention to development of the Ukrainian standard field in the future is paid.
Key words: Security service of Ukraine, legal regulation.